Introducing VERO: Visual experiential requirements organizer - Szóstek, Agnieszka; Karapanos, Evangelos (My University, 2011)
Crucial to the advancement of the User Experience field is the ability to understand product qualities as perceived by users. Therefore we would like to introduce VERO (Visual Experiential Requirements Organizer), an online tool for the structured elicitation of users' perceptions of a given stimulus such as a product, a system or a concept. Contrary to the existing elicitation methods, VERO aims to enable users to freely express opinions about qualities relevant for a given stimulus; to indicate the importance of each quality without imposing a hierarchical order and to cluster related qualities according to users' own perception regarding the strength of the link between them. In this paper we also motivate our approach in developing VERO and sketch our research agenda regarding its validation and application in the field of User Experience.
Keywords: HCI tools and methodologies; Product evaluation; User Experience; User requirements elicitation